A sensibilização ao cuidado parental modifica a percepção de imprevisibilidade e o início da vida reprodutiva de adolescentes? - Carvalho Neto, Adauto Barcellos de (2018)
The Life History Theory is based on the assumption that the resources required fordevelopment are scarce and therefore, organisms face tradeoffs in deciding how they will usethese resources. One of the tradeoffs involves deciding whether to invest in quantitative orqualitative reproductive strategy. There are indications that this decision is related to thepredictability of resources during childhood. While the perception of predictability would leadto a qualitative strategy, the perception of unpredictability would lead to a quantitativestrategy. In short, quantitative reproductive strategies would be related to initiating sexualactivity earlier and maintaining short-term love relationships, more children, and less parentalinvestment. Qualitative reproductive strategies relate to initiating later sex life, having fewerchildren, and greater parental investment (Davis & Werre, 2008). The objective of thisresearch was to evaluate the unpredictability beliefs and intention to achieve future milestonesof adolescents enrolled in public schools in the city of Vitória, ES. The sample comprised 96participants (67 girls and 29 boys) students from municipal schools of Vitória, ES, enrolled inthe 6th and 7th grades, whose mean age was 12 years (Min = 11, Max = 14, SD = 0.9). Datawere tabulated and processed using IBM SPSS Statistics, version 20. Descriptive analyzes(mean, standard deviation, percentage, and frequency) were made for each of the measuredvariables. The differences between the schools in which the collections were made forsociodemographic and scalar variables were analyzed through Mann-Whitney analyzes. Thecorrelation between family unpredictability in childhood and continuous sociodemographicvariables and the expectations of the future of adolescents were evaluated using Spearman'scorrelation analysis. The differences between the pre and post intervention measures wereevaluated using Wilcoxon analysis. The perception of family unpredictability in adolescents' childhood was significantly related to some variables evaluated. Adolescents who reportedhaving separate parents had significantly (Mann-Whitney U = 785.0 p = .01) higherperception of financial unpredictability during childhood (M = 2,5) than those who reportedhaving no separate parents (M = 2,1)…